Menggali Jejak Pengetahuan Lokal: Kajian Etnobotani Pemanfaatan Tumbuhan Pangan Liar di Desa Seloliman, Mojokerto - Dea Mawar Saharani; Luthfi Salsa Dewi; Nailah Zahroh Qurrotun A’yun; Nisaul Azmi Amalia; Fahrul Ghani Muhaimin; Ayu Chandra Mustikasari; Nafi’ Windy Kharisma; Syifa Nabila Firdausya; Heni Refdiana; Anas Bagaskara Witanto; Susriyati Mahanal (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2026)
This study aims to identify and document the diversity of wild plants used as food sources and analyze quantitative ethnobotanical indices based on local knowledge of the Seloliman Village community, Trawas District, Mojokerto Regency. This study used mixed methods with a sequential exploratory design approach. Qualitative data were obtained from observation, documentation, and interviews with purposive sampling techniques for key informants and snowball sampling for additional informants. Quantitative data were obtained through questionnaires to 89 respondents determined by the Slovin formula. Quantitative data analysis used ethnobotanical indices ICF, RFC, SUV, FUV, FL, and PPUV. The results showed that there were 48 species of wild food plants from 32 families with a dominant Asteraceae family. The ICF value of 0.85–0.96 indicated a high homogeneity of local knowledge among informants. The Yeng-yeng plant (Crassocephalum crepidioides) had the highest RFC value (0.67) and the highest SUV (0.66), making it the most culturally important species. The Asteraceae family had the highest FUV value of 0.87. The most widely utilized plant part was the leaves, with a PPUV of 75.39%. This research demonstrates that wild food plants have cultural value and strategic potential in supporting local food security and the ethnobotanical knowledge of the Seloliman community.